Metal-free azo-bridged porphyrin porous organic polymers for visible-light-driven CO2 reduction to CO with high selectivity. Issue 22 (27th May 2020) - Hou, Yuxia; Zhang, Enhui; Gao, Jiayin; Zhang, Shuaiqi; Liu, Ping; Wang, Ji-Chao; Zhang, Yuping; Cui, Cheng-Xing; Jiang, Jianzhuang
Abstract : Two nitrogen-rich azo-bridged POP displaying high photocatalytic reduction activity for CO2 to CO without a sacrificial reagent or metal co-catalyst were prepared. Abstract : Two nitrogen-rich azo-bridged porphyrin porous organic polymers (Azo-Por-Bpy-POP and Azo-Por-Dadp-POP ) with high surface areas were prepared by coupling 5, 10, 15, 20-tetra( p -nitrophenyl)-porphyrin with the aromatic amines of 2, 2′-bipyridine-5, 5′-diamine (Bpy) and diaminodiphenyl (Dadp). Azo-Por-Bpy-POP and Azo-Por-Dadp-POP display high photocatalytic reduction activity for CO2 to CO under visible-light irradiation without a sacrificial reagent or metal co-catalyst. Azo-Por-Bpy-POP exhibits the highest photoreduction for CO2 with CO as the only carbonaceous reduction product with a production rate of 38.75 μmol g −1 h −1 . Theoretical investigations indicate a stronger electrostatic interaction between CO2 and Azo-Por-Bpy-POP than Azo-Por-Dadp-POP, which favors CO2 photoreduction.